Regiodivergent electroreductive defluorinative carboxylation of gem-difluorocyclopropanes. Issue 8 (31st March 2023) - Zhao, Bin; Pan, Zichen; Pan, Jiayu; Deng, Hongping; Bu, Xiaoli; Ma, Mengtao; Xue, Fei
Abstract : A regiodivergent electrochemical defluorocarboxylation of gem -difluorocyclopropanes is realized, providing access to branched and linear carboxylated monofluorinated alkenes. Abstract : Access to regioselective monofluorinated alkenes concurrently from fluoroalkenylating building blocks such as gem -difluorocyclopropanes represents a powerful synthetic tool and yet a longstanding challenge. Herein, we report a regiodivergent defluorinative carboxylation of gem -difluorocyclopropanes achieved by subtly modulating the electrochemical conditions. A range of branched and linear monofluoroalkene carboxylic acids were produced in moderate to high isolated yields and with exclusive regioselectivities. The protocol was designed to be "green", by using atmospheric CO2 as the C1 source and not using transition metals. It was also found to be scalable and applicable to late-stage functionalization of complex compounds.